Testicular Sertoli Cell Hormones in Differences in Sex Development - Lucas-Herald, Angela K.; Mitchell, Rod T. (Frontiers in Endocrinology, 2022)
The Sertoli cells of the testes play an essential role during gonadal development, in addition to supporting subsequent germ cell survival and spermatogenesis. Anti-Müllerian hormone (AMH) is a member of the TGF-β superfamily, which is secreted by immature Sertoli cells from the 8th week of fetal gestation. lnhibin B is a glycoprotein, which is produced by the Sertoli cells from early in fetal development. In people with a Difference or Disorder of Sex Development (DSD), these hormones may be useful to determine the presence of testicular tissue and potential for spermatogenesis. However, fetal Sertoli cell development and function is often dysregulated in DSD conditions and altered production of Sertoli cell hormones may be detected throughout the life course in these individuals. As such this review will consider the role of AMH and inhibin B in individuals with DSD.